Socioeconomic Inequalities in Non-Adherence to Antihypertensive Medication in Peru - Intimayta-Escalante, Claudio; Quintana-Garcia, Lynn A. (Medicina Clínica y Social, 2024)
Introduction: In Peru, adherence to antihypertensive treatment ranges from 55.5% to 46.6%. Adherence decreases under adverse socioeconomic conditions. Objective: The aim of this research was to evaluate the socioeconomic inequalities in non-adherence to antihypertensive medication in Peru. Methods: A cross-sectional study was conducted through the analysis of data from the Demographic and Family Health Survey carried out in Peru between 2013 and 2023. We addressed the socioeconomic conditions of hypertensive Peruvian adults, including sex, age group, educational level, area or place of residence, and health insurance. These conditions were evaluated as sources of inequality in non-adherence to antihypertensive medication at a general level using the Concentration Index (CI) or Erreygers’ Concentration Index (ECI) among hypertensive adults over 29 years old. Results: In the 15,624 hypertensive adults older than 29 years included in the study, 86.63% were adherent to their antihypertensive medication. However, the inequality in medication non-adherence was considerable (CI: -0.259; 95%CI: -0.385 to -0.132; p
Keywords: Socioeconomic Health Disparities; Health Inequality Monitoring; Health Inequities; Hypertension; Treatment Adherence and Compliance; Antihypertensive Agents; Peru